2013
DOI: 10.2460/ajvr.74.9.1155
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and kinetic analysis of dogs during trotting after amputation of a thoracic limb

Abstract: Compared with results for quadruped dogs, the vertebral column, carpus, and ipsilateral hip and stifle joints had significant biomechanical changes after amputation of a thoracic limb. The ipsilateral pelvic limb assumed dual thoracic and pelvic limb roles because the gait of a thoracic limb amputee during trotting appeared to be a mixture of various gait patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 15 publications
2
36
1
Order By: Relevance
“…). Jarvis et al () and Hogy et al () recently described specific biomechanical changes after amputation of a thoracic and pelvic limb in dogs, respectively. Despite having obvious gait abnormalities, dogs and cats adapt well after an amputation (Withrow & Hirsch , Carberry & Harvey , Kirpensteijn et al .…”
Section: Introductionmentioning
confidence: 99%
“…). Jarvis et al () and Hogy et al () recently described specific biomechanical changes after amputation of a thoracic and pelvic limb in dogs, respectively. Despite having obvious gait abnormalities, dogs and cats adapt well after an amputation (Withrow & Hirsch , Carberry & Harvey , Kirpensteijn et al .…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic and kinematic studies have been completed to give objective data to pet owners as to how dogs will adapt following an amputation [6,11,12]. Kinetic changes after amputation indicate that amputee dogs use a compensatory mechanism that involves the unaffected diagonal limb pair [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…Since the current study was limited to an evaluation of stance, it is unclear how the gait at a walk and trot of forelimb and hind limb amputees that underwent a TPLO were impacted by the combination of an amputation and a TPLO. The gait adaptations of forelimb and hind limb amputees at trot have been described [6,12] and are complex. Briefly, in forelimb amputees, the ipsilateral hind limb assume the role of a forelimb and a hind limb [12].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a compensatory mechanism for the restriction of joint mobility in the forelimb, which was seen in the present study. Some researchers have reported that restriction of the forelimbs can lead to increased mobility of the hindlimbs [ 18 30 ]. Another explanation may be a compensatory mechanism for a restricted function of the hip joint.…”
Section: Discussionmentioning
confidence: 99%